Zad 1.

Uporządkuj jednomiany.

a) d * c* 2* c*c =

b) z* y * 0,5 * y * ( - 8)=

c) 14*a*a*b*b b ( - 3) *a =

d) 0,3*x*x*(- 4) * y*Y*y * ( - 5) =

Zad 2.

Zredukuj wyrazy podobne.

a) – 2 - 2a + 3+ 7a =

b) 2x – 4y - 2x – 4 – x – 22y + 5 =

2 2

c) 2x + 6x – 5x + 3x – 8=

d) 12ab – 3a + 14ab – 4a + 2b – 1 =

Zad 3. pksz wyrażenia , likwidując nawiasy. Zredukuj wyrazy podobne.

a) ( 2a + 2b) - ( 4a – 3b + 1) =

b) - ( 3x + 3y ) + ( 4x – 6y + 3) =

c) - ( 5ab + 14b) + ( - 7ab – 5b + 6) =

2 2

d) 3x y + ( 7x y – 5y + 5z) =